Techniques and Environments for Big Data Analysis Parallel, Cloud, and Grid Computing - Mishra, B. S.P; Dehuri, Satchidananda; Kim, Euiwhan; Wang, Gi-Name (Studies in Big Data,, 2016)
This volume is aiming at a wide range of readers and researchers in the area of Big Data by presenting the recent advances in the fields of Big Data Analysis, as well as the techniques and tools used to analyze it. The book includes 10 distinct chapters providing a concise introduction to Big Data Analysis and recent Techniques and Environments for Big Data Analysis. It gives insight into how the expensive fitness evaluation of evolutionary learning can play a vital role in big data analysis by adopting Parallel, Grid, and Cloud computing environments.